Teacher’s Perception towards Using English Songs as a Learning Media for Children - Azzahra, Syifa; Anisa Triyana; Susilawati, Susilawati (Candradimuka: Journal of Education, 2025)
Speaking ability is one of the basic skills that is very important for the development of children, there are many ways that can be done to improve speaking ability in children. One of them is to use songs as a learning medium because listening to songs and singing with children does not feel bored to learn but can make the atmosphere of the class and learning more fun so that the class becomes effective and the material conveyed is well conveyed. Then with this study, the researcher aims to find out the teacher's perception of the use of songs as a learning medium for children. This study aims to see how much the teacher's perception of song media as learning in improving English speaking in children. This study uses a qualitative design method, the instrument in this study is to use interviews with a total of 3 participants. The results of this study indicate that the use of English songs as media in learning is effective when applied in the classroom. By using a variety of songs related to the learning material can help children understand the material. In addition, through the use of songs, children can more quickly find new vocabulary and know how to pronounce the word. Songs can also create an active and effective learning atmosphere.